Aspirin versus vitamin K antagonist treatment guided by transoesophageal echocardiography in patients with atrial fibrillation: a pilot study. Issue 7 (31st January 2014) - Dinh, Trang; Baur, Leo H B; Pisters, Ron; Kamp, Otto; Verheugt, Freek W A; Smeets, Joep L R M; Cheriex, Emile C; Lindeboom, Jan-Eize; Heesen, Wilfred F; Tieleman, Robert G; Prins, Martin H; Crijns, Harry J G M; et al.
Abstract : Objective: Current stroke risk schemes need improvement of predictive value in patients with atrial fibrillation. Transoesophageal echocardiography (TEE) may facilitate stroke risk assessment in such patients and guide antithrombotic treatment. Methods: We randomised 238 patients with non-valvular atrial fibrillation and a moderate stroke risk to aspirin or adjusted vitamin K antagonist therapy after TEE had ruled out thrombogenic features in the atria and aorta. The primary outcome was a composite of stroke, major bleeding, peripheral embolism and all-cause mortality. Results: Mean CHA2 DS2 -VASc score was 2.1±1.1. The incidences of the composite primary outcome at a mean follow-up of 1.6 years were 3.2% (2.02% per year) in the aspirin group compared to 6.1% (3.84% per year) in the vitamin K antagonists group with an absolute advantage of 2.9 percentage points. Aspirin was non-inferior to vitamin K antagonists (p<0.0001) because the upper limit of the 90% CI did not exceed the 7% absolute difference in event rate between the two treatment arms. Conclusions: This hypothesis-generating pilot trial has found that TEE may be used for refinement of stroke risk in paroxysmal atrial fibrillation patients. A larger trial is needed to confirm these data. (ClinicalTrials.gov number NTC00224757).